2017
DOI: 10.1017/s1751731116002135
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and genetic variability of six chicken populations using single nucleotide polymorphism and copy number variants as markers

Abstract: 21Genomic and genetic variation among six Italian chicken native breeds (Livornese, 22 Mericanel della Brianza, Milanino, Bionda Piemontese, Bianca di Saluzzo and 23 Siciliana) were studied using single nucleotide polymorphism (SNP) and copy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
46
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 27 publications
14
46
3
Order By: Relevance
“…These results are different to the ones recently found by Strillacci et al [36] using the same approach in Italian well defined chicken breeds clearly clustered by CNVRs classification and by Tian et al [21] and Wang et al [49] in chicken and pigs respectively, showing additional evidence of the usefulness of CNV as markers for differentiating individuals. To provide a validation of the approach here used to cluster individuals of the Mexican population with CNVs we performed a PCA and a hierarchical clustering using the SNP genotypes: no clustering was obtained and the population resulted as for CNVs a unique genetic mix (Additional file 2: Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are different to the ones recently found by Strillacci et al [36] using the same approach in Italian well defined chicken breeds clearly clustered by CNVRs classification and by Tian et al [21] and Wang et al [49] in chicken and pigs respectively, showing additional evidence of the usefulness of CNV as markers for differentiating individuals. To provide a validation of the approach here used to cluster individuals of the Mexican population with CNVs we performed a PCA and a hierarchical clustering using the SNP genotypes: no clustering was obtained and the population resulted as for CNVs a unique genetic mix (Additional file 2: Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The large proportion of singleton CNVRs has been previously reported in chicken populations also by Yi et al [24], Han et al [22] and Strillacci et al [36], finding a total fraction of 68.8%, 76.5% and 75%, respectively. Our findings confirm their results and showed that also in the Mexican chicken population the segregation of CNVs exists among individuals.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This result is similar to the SNP-based PCA result (Xu et al, 2017, described in a separate manuscript). A recent study suggested that, like SNPs, CNV can separate Italian chicken populations similarly well [59]. Compared to their study, our study further confirms that CNV markers can be used to study the genetic variability in diverse chicken lines.…”
Section: Discussionsupporting
confidence: 84%
“…There were also some reports about CNV studies in inbred chicken lines using array CGH [36]. Additionally, a recent study has published in ten Italian chicken lines to study the population genetics based on SNP and CNV [59]. One of the main difficulties is that, unlike simple deletions and duplications, efficient genotyping tools with high accuracy are still lacking for complex CNVs (for example, multi-allelic CNVs) [60].…”
Section: Discussionmentioning
confidence: 99%